Koncepcja zagospodarowania wód opadowych w miejscowości Rozłogi k. Świebodzina = Concept rainwater management in a city Rozłogi near the Świebodzin - Kołodziejczyk, Urszula; Kołodziejczyk, Wiktor; Kuroczycki, Lech; Rudnicka, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Article shows how rainwater in an area with a large decrease in morphological, located in the city Rozłogi near the Świebodzin (Lubusz Voivodeship). This area is used by various businesses. Changing land use by one of them caused flooding low-lying areas, including the railway tracks located at the foot of the slope. Applied the concept of dehydration allowed properly utilize rainwater and reduce the conflict that occurs between users fine-tuned analysis of the area.
Keywords: wody opadowe; spadek morfologiczny; zagospodarowanie terenu; rain water; decrease in morphological; land development